53=-2-(1-7n)

Simple and best practice solution for 53=-2-(1-7n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53=-2-(1-7n) equation:


Simplifying
53 = -2 + -1(1 + -7n)
53 = -2 + (1 * -1 + -7n * -1)
53 = -2 + (-1 + 7n)

Combine like terms: -2 + -1 = -3
53 = -3 + 7n

Solving
53 = -3 + 7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7n' to each side of the equation.
53 + -7n = -3 + 7n + -7n

Combine like terms: 7n + -7n = 0
53 + -7n = -3 + 0
53 + -7n = -3

Add '-53' to each side of the equation.
53 + -53 + -7n = -3 + -53

Combine like terms: 53 + -53 = 0
0 + -7n = -3 + -53
-7n = -3 + -53

Combine like terms: -3 + -53 = -56
-7n = -56

Divide each side by '-7'.
n = 8

Simplifying
n = 8

See similar equations:

| 3*x+3=30 | | 50y+25x= | | y=-2x+22 | | 29t=319 | | 17+x=18*x | | 2(x+8)+7=43 | | x^3-12x^2+35= | | -6=-(p-1) | | 4p-8p+4p+6= | | 0=1960t-4.9t^2-h | | 9+(-2-8)=X | | x^2+44+16x=180 | | X^2-8x+10= | | 9=1+8(1+n) | | (W-2)(w+7)= | | 5(3+5x)=-85 | | 3y+2=-2y-7 | | 3[x-2]=-9 | | 6x+2x=9x-6 | | 4(-x+3)=36 | | m+40+90=180 | | 21=-8(4n-3)-3 | | 6X-7=5(2X+7) | | 7x+3x-8x-5=9 | | 3(4+6a)+6a=-36+8a | | (-124)-(-254)= | | 14x+10=-7 | | 2x+5x-3x-5=7 | | 3xa=12 | | -8(-8-8x)=-8-8x | | 1-5n=-2(4-2n) | | P^2+16p-33=0 |

Equations solver categories